Microstructure measurement and microgeometric packing characterization of rigid polyurethane foam defects - Xu, Jie; Wu, Tao; Zhang, Jianwei; Chen, Hao; Sun, Wei; Peng, Chuang (Smithers Rapra, 2017)
Streak and blister cell defects pose extensive surface problems for rigid polyurethane foams. In this study, these morphological anomalies were visually inspected using 2D optical techniques, and the cell microstructural coefficients including degree of anisotropy, cell circumdiameter, and the volumetric isoperimetric quotient were calculated from the observations. A geometric regular polyhedron approximation method was developed based on relative density equations, in order to characterize the packing structures of both normal and anomalous cells. The reversely calculated cell volume constant, Cc, from polyhedron geometric voxels was compared with the empirical polyhedron cell volume value, Ch. The geometric relationship between actual cells and approximated polyhedrons was characterized by the defined volumetric isoperimetric quotient. Binary packing structures were derived from deviation comparisons between the two cell volume constants, and the assumed partial relative density ratios of the two individual packing polyhedrons. The modelling results show that normal cells have a similar packing to the Weaire-Phelan model, while anomalous cells have a dodecahedron/icosidodecahedron binary packing.